Low-temperature adaptive early-strength accelerator for sprayed concrete as well as preparation method and application of low-temperature adaptive early-strength accelerator
By compounding components such as nano-silane-modified calcium bromide aluminate crystal nuclei into a quick-setting agent for shotcrete, the problems of slow hydration, insufficient early strength, and high rebound rate at low temperatures have been solved, achieving improved low-temperature adaptability, early high strength, and durability, making it suitable for shotcrete construction in cold regions.
Patent Information
- Application Number
- CN202511610874.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-01-23
AI Technical Summary
Shotcrete suffers from high rebound rate, low early strength, and insufficient long-term durability in low-temperature environments. Especially in the range of -5℃ to 5℃, existing technologies cannot simultaneously achieve a synergistic improvement in low-temperature adaptability, early high strength, rapid setting, and low rebound performance.
The compound is made of nano-silane modified calcium oxybromoaluminate crystal nuclei, aluminum sulfate, triethanolamine, modified polyacrylamide and nano silica fume, etc. Through a specific preparation process, including step-by-step feeding, temperature control and ultrasonic dispersion, the inorganic accelerator and organic activator work together to promote cement hydration reaction, improve early strength and enhance durability.
It significantly reduces the rebound rate of shotcrete in low-temperature environments, improves early strength, ensures long-term freeze-thaw resistance and impermeability, and eliminates the risk of steel reinforcement corrosion, making it suitable for shotcrete construction in cold regions.
Smart Images

Figure CN121377602A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of sprayed concrete, in particular to a low-temperature adaptive early-strength accelerator for sprayed concrete, a preparation method and application thereof. BACKGROUND
[0002] Sprayed concrete is a special kind of concrete that uses spraying machinery to spray mixed materials at high speed to the sprayed surface to harden and solidify. It has become a key material in the field of civil engineering such as tunnel primary support, slope protection reinforcement, and existing building structure repair, due to its rapid forming, no need for traditional formwork support, and strong adaptability to complex working conditions. With the extension of transportation, energy, and urban construction infrastructure to high altitudes and cold regions, the application scenarios of sprayed concrete are continuously expanding. However, the three core problems of high construction rebound rate, low early strength, and insufficient long-term durability have long existed, which not only restricts the construction efficiency and engineering quality, but also exacerbates the problems in low-temperature working conditions, becoming a key bottleneck hindering its widespread application in cold regions. From the internal contradiction between material performance and construction technology, the pumpability of sprayed concrete requires it to maintain a certain water-binder ratio (usually higher than ordinary formwork concrete) to avoid pipe blockage and material interruption during spraying, ensuring construction continuity. However, a higher water-binder ratio not only increases the internal porosity of the concrete, directly weakening its long-term durability such as impermeability and frost resistance, but also accelerates the condensation of water in low-temperature environments, significantly inhibiting the cement hydration reaction, further reducing the early strength development rate (often with a 24h strength of less than 30% of the design value after spraying), and possibly causing internal microcracks due to the volume expansion of frozen water, forming a vicious cycle of "low early strength—poor long-term durability". Meanwhile, the unique jet forming method of sprayed concrete makes it prone to air entrapment during the formation of the sprayed surface, resulting in a large number of interconnected pores and weak interfaces inside, which become a "breakthrough" for freeze damage under the action of low-temperature freeze-thaw cycles, accelerating the deterioration of concrete performance. To address the above problems, existing technologies have made many improvement attempts. For example, a Chinese invention patent with publication number CN118757183A discloses a low-rebound high-performance sprayed concrete, which effectively controls the rebound rate below 10% by compounding rebound suppression materials and mineral admixtures, and combining with a mechanized spraying system with real-time parameter monitoring and control function, significantly improving construction economy and forming quality. However, this technical solution does not optimize the slow cement hydration problem in low-temperature environments, and the early strength improvement effect is not obvious, making it difficult to meet the demand for rapid support or structural bearing in environments below 5℃.
[0003] The Chinese invention patent with the publication number CN119143440A proposes a green low-carbon high-performance sprayed concrete using active regenerated micro powder, which optimizes the cementing system by utilizing the pozzolanic activity of regenerated micro powder, thereby reducing carbon emissions and improving the late strength and durability of concrete to some extent. However, this technology does not solve the core problem of lagging early strength development at low temperatures, and the introduction of regenerated micro powder may slightly prolong the hydration induction period of cement, which may exacerbate the problem of insufficient early strength under low temperature conditions. The improvement of durability is also weakened due to the superimposed effect of low temperature freezing. Further analysis of the special challenges of sprayed concrete in low temperature environments shows that the core shortcoming of current technology is the lack of functional additives that can simultaneously achieve "low temperature adaptability - early high strength - rapid setting". Traditional accelerators can shorten the setting time, but the rapid setting effect is significantly reduced at low temperatures, and may lead to a decrease in the late strength of concrete. Conventional early strength agents (such as chloride salts and sulfate salts) can promote early strength development, but chloride-based early strength agents can cause steel corrosion, sulfate-based early strength agents have low efficiency at low temperatures, and neither can solve the problem of rebound rate control and durability improvement of sprayed concrete at low temperatures.
[0004] Therefore, it is an urgent need to develop a low-temperature adaptive early strength accelerator that can effectively promote the rapid setting and hardening of sprayed concrete in low temperature environments (especially in the range of -5℃ to 5℃), significantly improve the early strength (such as 1d strength reaching more than 50% of the design value), while ensuring low rebound performance and long-term durability, and has no risk of steel corrosion, to break through the application bottleneck of sprayed concrete in cold regions and promote the development of high-performance materials in the field of civil engineering. SUMMARY
[0005] The purpose of the present application is to overcome the shortcomings of the prior art and provide a low-temperature adaptive early strength accelerator for sprayed concrete, a preparation method and its use.
[0006] To achieve the above-mentioned purpose, the following technical solutions are adopted: A low-temperature adaptive early strength accelerator for high-performance sprayed concrete, comprising the following components by mass fraction: Nano-silane modified calcium bromoaluminate crystal nucleus 15-22 parts, aluminum sulfate 30-40 parts, triethanolamine 2-5 parts, modified polyacrylamide (molecular weight 8 million) 1-3 parts, nano-silica fume 5-8 parts, sodium citrate 0.5-1.2 parts, and deionized water 48-85 parts.
[0007] Preferably, the raw materials for preparing the nano-silane modified calcium oxybromolum aluminate crystal nucleus include: calcium bromide (analytical pure, CaBr2≥99%), tricalcium aluminate (industrial grade, Ca3Al2O6≥95%), γ-aminopropyl triethoxysilane (KH550, industrial grade), anhydrous ethanol (analytical pure), and deionized water. The preparation steps are as follows: S1, 100 parts by weight of deionized water is heated to 60±2℃, 35 parts by weight of calcium bromide is added, and magnetic stirring is carried out until complete dissolution to form a bromide ion stock solution; Slowly add 28 parts by weight of tricalcium aluminate powder to the stock solution, control the stirring speed at 800r / min, and react at constant temperature for 2.5h to generate Ca4Al2O6Br2•10H2O precursor suspension; Filter with a plate and frame filter press, collect the filter cake, wash with deionized water for 3 times (to remove free bromide ions), vacuum dry at 80℃ for 4h, crush and pass through a 200 mesh sieve to obtain calcium oxybromolum aluminate powder.
[0008] S2, the above calcium oxybromolum aluminate powder is added to a high-speed ball mill, ethanol is used as the dispersion medium (solid-liquid ratio 1:5), 0.5 parts by weight of dispersant (sodium hexametaphosphate) is added, ball milling is carried out for 4h (ball-to-material ratio 8:1, rotation speed 500r / min), and a nano-suspension with particle size of 80-150nm is formed; Transfer the suspension to a three-necked flask, heat to 75℃, and add 3-5% KH550 ethanol solution (KH550: ethanol = 1:4) of the weight of calcium oxybromolum aluminate, continue to stir for 1.5h to realize silane molecule grafting; After the reaction is completed, centrifugal separation is carried out, and the product is washed with anhydrous ethanol for 2 times, vacuum dried at 105℃ for 6h, and a white fluffy nano-silane modified calcium oxybromolum aluminate crystal nucleus is obtained.
[0009] Preferably, the particle size of the aluminum sulfate is ≤5μm.
[0010] Preferably, the molecular weight of the modified polyacrylamide is 8 million.
[0011] Preferably, the deionized water meets the following requirements: conductivity ≤10μS / cm (25℃), total hardness (as CaCO3) ≤5mg / L, pH value 6.5-7.5, chloride ion content ≤0.5mg / L, and sulfate ion content ≤2mg / L.
[0012] Preferably, the preparation method of the accelerator is as follows: S1, solvent preheating and basic component dissolution Into the reactor, 48-85 parts by weight of deionized water (the specific amount is determined according to the formula, and 60 parts by weight is taken as an example here) is added, the heating jacket is turned on, the water temperature is raised to 45±2℃, and the stirring is started (the stirring rate is 500 r / min). 0.5-1.2 parts by weight of sodium citrate is slowly added, and the stirring is continued for 15 min until the sodium citrate is completely dissolved to form a clear and transparent sodium citrate aqueous solution (complete dissolution can be observed by visual observation, and there is no obvious solid particles). S2, mixing of the core early strength component and the main accelerator The temperature of the reactor is kept at 45±2℃, and the stirring rate is 500 r / min. First, 15-22 parts by weight of nano-silane modified calcium bromoaluminate crystal nucleus is added, and the stirring is continued for 10 min to preliminarily disperse the crystal nucleus in the solution (the dispersion effect can be monitored in real time by a laser particle size analyzer to ensure that there is no obvious agglomeration of the particle size). Then, 30-40 parts by weight of alkali-free aluminum sulfate is added in three portions (each portion is separated by 5 min, and 1 / 3 of the total amount is added each time), and the stirring is continued for 5 min after each addition to avoid local high concentration leading to caking; after all the additions, the stirring rate is increased to 700 r / min, and the stirring is continued for 20 min to form a uniform white suspension. S3, addition of functional additives and stabilization of the system The stirring rate is reduced to 600 r / min, the temperature is kept at 45±2℃, and 2-5 parts by weight of triethanolamine is added dropwise (the dropwise addition rate is controlled at 1-2 mL / s to avoid the sudden increase of local alkalinity leading to the precipitation of aluminum ions), and the stirring is continued for 10 min after the dropwise addition. Then, 5-8 parts by weight of nano-silica is added, and the stirring is continued for 15 min. During this period, the ultrasonic dispersion device (power 300 W, frequency 20 kHz) in the reactor can be started to assist the dispersion, so as to ensure that there is no agglomeration of the nano-silica (the dispersion is qualified if there is no obvious stratification or precipitation in the suspension by sampling observation). S4, addition of the rebound suppression component and final adjustment The stirring rate is kept at 600 r / min, and the temperature is kept at 45±2℃. 1-3 parts by weight of modified polyacrylamide (molecular weight 8 million) is slowly added while stirring to avoid the caking of polyacrylamide when it comes into contact with water. After all the additions, the stirring is continued for 20 min to completely dissolve the polyacrylamide and form a uniform viscous liquid. Turn off the heating jacket and allow it to cool naturally to room temperature (25±5℃), maintaining a stirring rate of 300 r / min during this period. After cooling, test the viscosity of the accelerator (required to be 500-800 mPa•s, measured using a rotational viscometer at 60 r / min). If the viscosity is too high, add a small amount of deionized water (each addition should not exceed 1 part by weight), stir for 5 minutes, and then test again until the viscosity meets the requirements. S5, Filtration and Packaging The prepared quick-setting agent is filtered through a 100-mesh nylon filter to remove any small amounts of lumps or impurities, ensuring product uniformity.
[0013] This invention patent can function stably in low-temperature environments ranging from -5℃ to 5℃, effectively solving the problems of slow solidification and insufficient early strength of traditional quick-setting agents at low temperatures.
[0014] Nano-silane-modified calcium oxybromoaluminate (CSH) crystal nuclei have small particle sizes and large specific surface areas, serving as "seeds" for CSH gel growth in concrete systems. They provide numerous active sites for cement hydration, inducing rapid hydration reactions around the nuclei in cement particles, accelerating CSH gel formation and aggregation, thus shortening the hydration induction period and improving early strength. Simultaneously, the bromine in the nuclei lowers the freezing point of water within the concrete, reducing the inhibitory effect of water freezing on the hydration reaction at low temperatures. Furthermore, bromide ions can form stable compounds with calcium ions in cement hydration products, preventing decomposition of these products at low temperatures. The silane-modified layer improves the interfacial compatibility between the nuclei and cement paste, reducing weak interfacial areas and enhancing the sustained induction effect of the nuclei on the hydration reaction, ensuring stable early strength performance at low temperatures. Alkali-free aluminum sulfate, used as a quick-setting agent, releases Al after dissolving in water. 3+ Al 3+ Triethanolamine reacts rapidly with Ca(OH)₂ produced during cement hydration to form hydrated calcium sulfoaluminate (AFt). AFt crystals are rapidly generated and interwoven into a network, quickly filling the pores of the cement paste and promoting rapid concrete setting. Triethanolamine, as an organic setting accelerator, can, on the one hand, undergo a complexation reaction with tricalcium aluminate and tricalcium silicate in cement, disrupting the hydration film on the surface of cement particles and accelerating the dissolution and hydration of cement minerals; on the other hand, its weak alkalinity can adjust the pH of the paste to the optimal hydration range of 10-11, promoting Al₂O₃ hydration. 3+ With Ca 2+ The reaction rate is increased, enhancing the rapid setting effect of alkali-free aluminum sulfate and forming a synergistic effect of "inorganic coagulation promotion + organic activation" to optimize the rapid setting performance. Sodium citrate, as a complexing agent, can react with excess free calcium during cement hydration. 2+ Forming stable complexes, avoiding Ca 2+The calcium carbonate crystals are precipitated in the concrete, reducing the damage of the crystal expansion to the internal structure of the concrete, delaying the strength reduction of the cement in the later stage of hydration, and ensuring the 28d strength retention rate. The nano-silica ash has very high pozzolanic activity and specific surface area. In the later stage of cement hydration, it can have a secondary hydration reaction with Ca(OH)2 to generate additional C-S-H gel. These gels can fill the capillary pores and microcracks in the concrete, refine the pore size structure, reduce the porosity, reduce the invasion channels of water and harmful ions, and thus improve the durability of the concrete, such as impermeability and frost resistance, and cooperates with sodium citrate to build a durability protection system of "complexation control of calcium in the early stage - filling and densification in the later stage". After the modified polyacrylamide is dissolved in the accelerator system, a high molecular chain structure with certain viscosity is formed. These high molecular chains can be adsorbed on the surface of cement particles and aggregates, and through the intermolecular attraction and hydrogen bond action, the cohesiveness and wrapping property of the cement slurry are enhanced, and the separation phenomenon of aggregates and slurry in the spraying process is reduced. At the same time, it can form an elastic network structure in the slurry, buffer the impact force during spraying, reduce the rebound probability of aggregates, and control the rebound rate below 8%, not only reducing material waste, but also ensuring the uniformity of the sprayed concrete after molding, avoiding the problem of insufficient local structural strength caused by rebound. BRIEF DESCRIPTION OF DRAWINGS
[0015] Figure 1 is the physical map of the prepared accelerator; Figure 2 is the field application diagram of the accelerator. DETAILED DESCRIPTION
[0016] The present application will be further described below by examples.
[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present application more clear, the technical scheme in the embodiments of the present application will be described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present application, not all the embodiments.
[0018] The cement is P.O42.5 ordinary portland cement; the aggregate is continuous graded gravel (particle size 5-10mm) and medium sand (fineness modulus 2.6); the accelerator is prepared according to the formulation of the examples and the comparative examples; the mixing water is ordinary drinking water. Simulate -5℃, 0℃, 5℃ three kinds of low temperature environment, refer to "Accelerator for Shotcrete" (GB / T 35159-2017) and "Standard Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019) to test the performance, the test indexes include rebound rate, 8h compressive strength, frost resistance (mass loss rate and strength loss rate after 200 times of freeze-thaw cycle), 28d electric flux (evaluation of impermeability).
[0019] Example 1: nano-silane modified calcium oxybromaluminate crystal nucleus 15 parts, aluminum sulfate 30 parts, triethanolamine 2 parts, modified polyacrylamide 1 part, nano-silica 5 parts, sodium citrate 0.5 parts, deionized water 48 parts; Example 2: nano-silane modified calcium oxybromaluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, nano-silica 6.5 parts, sodium citrate 0.8 parts, deionized water 65 parts; Example 3: nano-silane modified calcium oxybromaluminate crystal nucleus 22 parts, aluminum sulfate 40 parts, triethanolamine 5 parts, modified polyacrylamide 3 parts, nano-silica 8 parts, sodium citrate 1.2 parts, deionized water 85 parts.
[0020] Comparative Example 1 (no core early strength component): aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, nano-silica 6.5 parts, sodium citrate 0.8 parts, deionized water 65 parts (remove nano-silane modified calcium oxybromaluminate crystal nucleus, the rest is the same as Example 2); Comparative Example 2 (low dosage of durability-increasing component): nano-silane modified calcium oxybromaluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, nano-silica 3 parts, sodium citrate 0.3 parts, deionized water 65 parts (nano-silica and sodium citrate dosage is lower than the limited range of Example 2); Comparative Example 3 (high dosage of durability-increasing component): nano-silane modified calcium oxybromaluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, nano-silica 10 parts, sodium citrate 1.5 parts, deionized water 65 parts (nano-silica and sodium citrate dosage is higher than the limited range of Example 2); Comparative Example 4 (low dosage of rebound suppression component): nano-silane modified calcium oxybromaluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 0.5 parts, nano-silica 6.5 parts, sodium citrate 0.8 parts, deionized water 65 parts (modified polyacrylamide dosage is lower than the limited range of Example 2); Comparative Example 5 (high dosage of rebound suppression component): nano-silane modified calcium oxybromaluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 4 parts, nano-silica 6.5 parts, sodium citrate 0.8 parts, deionized water 65 parts (modified polyacrylamide dosage is higher than the limited range of Example 2); Comparative Example 6 (conventional non-alkali accelerator): commercially available non-alkali accelerator (main component: aluminum sulfate, without nano-silane modified calcium bromo-aluminate crystal nucleus and nano-silica).
[0021] Comparative Example 7 (without triethanolamine): Nano-silane modified calcium bromo-aluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, modified polyacrylamide 2 parts, nano-silica 6.5 parts, sodium citrate 0.8 parts, deionized water 65 parts (remove triethanolamine, the rest is the same as Example 2); Comparative Example 8 (without nano-silica): Nano-silane modified calcium bromo-aluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, sodium citrate 0.8 parts, deionized water 65 parts (remove nano-silica, the rest is the same as Example 2); Comparative Example 9 (without sodium citrate): Nano-silane modified calcium bromo-aluminate crystal nucleus 18 parts, aluminum sulfate 35 parts, triethanolamine 3.5 parts, modified polyacrylamide 2 parts, nano-silica 6.5 parts, deionized water 65 parts (remove sodium citrate, the rest is the same as Example 2); Comparative Example 10 (process comparison: no order mixing) Scheme: use the same components and proportions as Example 2.
[0022] Process: do not follow the feeding order and conditions of S1-S5 of the present application, but all solid powders (nano-silane modified calcium bromo-aluminate crystal nucleus, aluminum sulfate, nano-silica, sodium citrate) are put into deionized water at room temperature at one time, then stirred at 500 r / min for 30 minutes. Then add triethanolamine and modified polyacrylamide, continue to stir for 20 minutes. Filter, directly as finished product.
[0023] Comparative Example 11 (process comparison: missing key steps) Scheme: use the same components and proportions as Example 2.
[0024] Process: basically follow the steps of the present application, but do not start the ultrasonic dispersion device to disperse nano-silica in S3, only rely on mechanical stirring.
[0025] The above test results are shown in Table 1. Table 1 Test results of different groups Group Ambient temperature Rebound rate (%) 8h compressive strength (MPa) Frost resistance (after 200 cycles of freezing and thawing) - mass loss rate (%) Frost resistance (after 200 cycles of freezing and thawing) - strength loss rate (%) 28d electric flux (C) Example 1 -5℃ 7.2 12.5 2.1 8.5 850 Example 1 0℃ 6.8 14.2 1.8 7.2 820 Example 1 5℃ 6.5 15.8 1.5 6.8 780 Example 2 -5℃ 6.9 13.8 1.9 7.8 830 Example 2 0℃ 6.5 15.5 1.6 6.5 790 Example 2 5℃ 6.2 17.2 1.3 5.9 750 Example 3 -5℃ 7.5 12.8 2.3 9.2 860 Example 3 0℃ 7.0 14.5 2.0 8.0 810 Example 3 5℃ 6.7 16.0 1.6 7.1 790 Comparative Example 1 -5℃ 12.5 5.8 5.8 25.6 1580 Comparative Example 1 0℃ 11.8 7.2 4.9 22.3 1450 Comparative Example 1 5℃ 11.2 8.5 4.2 19.8 1320 Comparative Example 2 -5℃ 9.8 10.2 4.5 18.7 1250 Comparative Example 2 0℃ 9.2 11.8 3.8 16.5 1180 Comparative Example 2 5℃ 8.8 13.2 3.2 14.2 1100 Comparative Example 3 -5℃ 10.5 9.5 5.2 22.8 1380 Comparative Example 3 0℃ 9.8 11.0 4.5 20.3 1300 Comparative Example 3 5℃ 9.3 12.5 3.8 17.5 1220 Comparative Example 4 -5℃ 11.2 11.8 4.8 20.5 1320 Comparative Example 4 0℃ 10.5 13.5 4.1 18.2 1250 Comparative Example 4 5℃ 9.8 15.0 3.5 15.8 1180 Comparative Example 5 -5℃ 10.8 10.5 5.0 21.7 1350 Comparative Example 5 0℃ 10.2 12.2 4.3 19.5 1280 Comparative Example 5 5℃ 9.5 13.8 3.7 17.2 1200 Comparative Example 6 -5℃ 15.2 4.2 7.5 32.8 1850 Comparative Example 6 0℃ 14.5 5.8 6.8 29.5 1720 Comparative Example 6 5℃ 13.8 7.5 6.2 26.8 1600 Comparative Example 7 -5℃ 9.5 9.8 4.2 18.5 1300 Comparative Example 7 0℃ 9.0 11.2 3.6 16.2 1220 Comparative Example 7 5℃ 8.6 12.8 3.1 14.0 1150 Comparative Example 8 -5℃ 8.2 11.5 5.5 22.0 1400 Comparative Example 8 0℃ 7.8 13.2 4.8 19.5 1320 Comparative Example 8 5℃ 7.4 14.8 4.2 17.0 1250 Comparative Example 9 -5℃ 8.0 10.8 6.0 24.5 1480 Comparative Example 9 0℃ 7.6 12.5 5.2 21.8 1380 Comparative Example 9 5℃ 7.2 14.0 4.5 19.0 1300 Comparative Example 10 -5℃ 11.5 8.5 6.2 26.5 1550 Comparative Example 10 0℃ 10.8 9.8 5.5 23.8 1450 Comparative Example 10 5℃ 10.2 11.2 4.8 21.0 1350 Comparative Example 11 -5℃ 8.0 11.0 3.5 14.5 1050 Comparative Example 11 0℃ 7.6 12.7 3.0 12.8 980 Comparative Example 11 5℃ 7.3 14.3 2.6 11.2 920 Comparative Example 1-3 and Comparative Example 1 (no core early strength component): the rebound rate of the examples is significantly lower than that of Comparative Example 1 (40%-55% lower), the 8h compressive strength is significantly higher than that of Comparative Example 1 (115%-138% higher), and the frost resistance and permeability resistance (28d electric flux) are also much better than those of Comparative Example 1, indicating that the nano-silane modified calcium bromine oxygen aluminum acid crystal nucleus is crucial for improving the early strength performance at low temperature, reducing the rebound rate, and optimizing the durability performance, and the "nucleation induction-low temperature activation" mechanism effectively solves the problem of slow cement hydration at low temperature.
[0026] Comparative Example 2 and Comparative Example 2 (low dosage of solid durability component), Comparative Example 3 (high dosage of solid durability component): the rebound rate of Example 2 is lower than that of Comparative Example 2 (25%-30% lower) and Comparative Example 3 (30%-35% lower), the 8h compressive strength is higher than that of Comparative Example 2 (17%-38% higher) and Comparative Example 3 (24%-50% higher), and the frost resistance and permeability resistance are also better. It is proved that the nano-silica and sodium citrate need to be controlled within the range of 1-5 specified dosage, which is too low to fill and complex calcium control, and too high to affect cement hydration and paste fluidity, which confirms the effectiveness of the "early complex calcium control-late filling and compaction" durability protection system.
[0027] Comparative Example 2 and Comparative Example 4 (low dosage of rebound suppression component), Comparative Example 5 (high dosage of rebound suppression component): the rebound rate of Example 2 is lower than that of Comparative Example 4 (30%-35% lower) and Comparative Example 5 (25%-30% lower), and the 8h compressive strength and durability performance are better. It is proved that too high or too low dosage of modified polyacrylamide will affect the cohesiveness and workability of the paste, only within the range of 1-3 parts, can the high molecular chain adsorption and elastic network effect effectively reduce the aggregate separation and rebound, while ensuring the strength and durability.
[0028] Comparative Example 1-3 and Comparative Example 6 (traditional non-alkali accelerator): the rebound rate of the examples is 45%-55% lower, the 8h compressive strength is 198%-229% higher, the frost resistance (mass loss rate is 70%-72% lower, strength loss rate is 70%-74% lower) and permeability resistance (28d electric flux is 42%-54% lower) are greatly improved, which fully proves the comprehensive advantages of the accelerator in low temperature adaptability, early strength, low rebound and high durability, far superior to traditional non-alkali accelerators.
[0029] Comparative Example 2 and Comparative Example 7 (no triethanolamine): The 8h compressive strength of the comparative example 7 at low temperature is about 20%-30% lower than that of the embodiment 2, the rebound rate is about 30% higher, the frost resistance and the impermeability are also obviously deteriorated, which indicates that the triethanolamine has an irreplaceable role in synergistically promoting rapid setting, improving early strength and adjusting the pH of the slurry.
[0030] The comparative example 2 and the comparative example 8 (without nano-silica ash): The frost resistance (mass loss rate and strength loss rate) and the impermeability (28d electric flux) of the comparative example 8 are significantly worse than those of the embodiment 2, which indicates that the nano-silica ash has a key role in filling pores, improving density and durability in the later stage.
[0031] The comparative example 2 and the comparative example 9 (without sodium citrate): The frost resistance and the impermeability of the comparative example 9 are obviously decreased, and the 28d strength retention rate is low, which indicates that the sodium citrate has an important role in controlling calcium ions, preventing strength reduction and improving durability.
[0032] The comparative example 2 and the comparative example 10 (without the orderly mixing process): The appearance of the rapid setting agent prepared by the comparative example 10 is uneven, and there is obvious precipitation at the bottom. The rebound rate of the comparative example 10 at each low temperature environment is about 40%-50% higher than that of the embodiment 2, the 8h compressive strength is about 35%-45% lower, the frost resistance and the impermeability are also significantly deteriorated. This shows that the preparation process of the present application is important for ensuring the full dissolution, dispersion and reaction of each component, and avoids the failure of components and performance degradation caused by local high concentration or chaotic reaction sequence.
[0033] The comparative example 2 and the comparative example 11 (without ultrasonic dispersion): The 8h compressive strength of the comparative example 11 is about 15%-20% lower than that of the embodiment 2, the frost resistance (strength loss rate) and the impermeability (28d electric flux) are also obviously deteriorated. This shows that the ultrasonic dispersion process can effectively break the agglomerates of nano-silica ash, so that it is uniformly distributed in the system, fully plays its pozzolanic effect and micro aggregate filling effect, and has a key role in ensuring the early strength and durability of the rapid setting agent.
[0034] Therefore, the low-temperature adaptive early strength rapid setting agent for high-performance shotcrete provided by the present application solves the problems of slow hydration, insufficient early strength, high rebound rate and poor durability of shotcrete in low-temperature environment (-5℃ to 5℃) by reasonably compounding nano-silica modified calcium bromo-aluminate crystal nucleus, aluminum sulfate, triethanolamine and other core components, and optimizing the preparation process.
[0035] This accelerator can stably exert its early strength and rapid setting effect under low temperature conditions, significantly reducing the rebound rate of sprayed concrete, while ensuring the long-term durability of concrete such as freeze-thaw resistance and impermeability, and eliminating the risk of steel reinforcement corrosion. Its preparation process is mature and controllable. It is suitable for shotcrete construction scenarios such as tunnel support and slope reinforcement in cold regions, improving construction efficiency and structural safety and reliability, reducing material waste, and possessing good engineering application value and promising prospects for promotion.
[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A low-temperature adaptable early-strength accelerator for sprayed concrete, characterized by, The following components are included by mass fraction: Nano-silane modified calcium oxybromalumate crystal nucleus 15-22 parts; Aluminum sulfate 30-40 parts; Triethanolamine 2-5 parts; Modified polyacrylamide 1-3 parts; Nano-silica 5-8 parts; Sodium citrate 0.5-1.2 parts; Deionized water 48-85 parts; The modified polyacrylamide has a molecular weight of 8 million, and the aluminum sulfate has a particle size of ≤5 μm.
2. The low-temperature adaptable early strength accelerator for shotcrete according to claim 1, characterized by, The raw materials for preparing the nano-silane modified calcium oxybromalumate crystal nucleus include, by mass fraction: Calcium bromide 35 parts; Tricalcium aluminate 28 parts; Sodium hexametaphosphate 0.5 parts; γ-aminopropyl triethoxysilane 4 parts; Anhydrous ethanol 16 parts; Deionized water 100 parts.
3. The low-temperature adaptable early strength accelerator for shotcrete according to claim 1 or 2, characterized by, The preparation steps of the nano-silane modified calcium oxybromalumate crystal nucleus are as follows: S1, heat 100 parts of deionized water to 58-62℃, add 35 parts of calcium bromide, and magnetically stir until completely dissolved to form a bromide ion stock solution; slowly add 28 parts of tricalcium aluminate powder to the stock solution, control the stirring speed at 800 r / min, and react at a constant temperature for 2.5 h to generate Ca4Al2O6Br2•10H2O precursor suspension; filter with a plate and frame filter press, wash the filter cake with deionized water 3 times, vacuum dry at 80℃ for 4 h, crush and pass through a 200 mesh sieve to obtain calcium oxybromalumate powder; S2, add the above calcium oxybromalumate powder to a high-speed ball mill, use 16 parts of ethanol as a dispersion medium, add 0.5 parts of dispersant sodium hexametaphosphate, and ball mill for 4 h to form a nano-suspension with a particle size of 80-150 nm; transfer the suspension to a three-necked flask, heat to 75℃, and drop 4% of the weight of the calcium oxybromalumate γ-aminopropyl triethoxysilane ethanol solution, continue to stir for 1.5 h; after the reaction is completed, centrifugal separation is performed, washed with anhydrous ethanol 2 times, and vacuum dried at 105℃ for 6 h to obtain nano-silane modified calcium oxybromalumate crystal nucleus.
4. The low-temperature adaptable early strength accelerator for shotcrete according to claim 3, characterized by, The ball-to-material ratio in the high-speed ball mill of step S2 is 8:1, and the rotation speed is 500 r / min.
5. The low temperature adaptable early strength accelerator for shotcrete according to claim 3, wherein In step S2, the mass ratio of γ-aminopropyl triethoxysilane to ethanol in the γ-aminopropyl triethoxysilane ethanol solution is 1:
4.
6. The low temperature adaptable early strength accelerator for sprayed concrete according to claim 1 or 2, characterized by, The deionized water meets the following requirements: at 25℃, the conductivity is ≤10 μS / cm, the total hardness is ≤5 mg / L in terms of CaCO3, the pH value is 6.5-7.5, the chloride ion content is ≤0.5 mg / L, and the sulfate ion content is ≤2 mg / L.
7. The method of claim 1, wherein the low temperature adaptable early strength accelerator for sprayed concrete is prepared by the steps of: The following steps are included: S1, add 48-85 parts of deionized water to the reaction kettle, turn on the heating jacket, raise the water temperature to 43-47℃, and turn on the stirring; slowly add 0.5-1.2 parts of sodium citrate, continue to stir for 15 min, and until the sodium citrate is completely dissolved; S2, keep the temperature of the reactor 43-47℃, the stirring speed 500r / min, add 15-22 parts by weight of nano-silane modified calcium bromine oxygen aluminate crystal nucleus, stir for 10 min; add 30-40 parts by weight of aluminum sulfate in 3 times, stir for 5 min after each addition; after all the addition, increase the stirring speed to 700r / min, continue stirring for 20 min; S3, reduce the stirring speed to 600r / min, keep the temperature 43-47℃, add 2-5 parts by weight of triethanolamine dropwise, stir for 10 min after the dropwise addition is completed; add 5-8 parts by weight of nano-silica fume, stir for 15 min, during which the ultrasonic dispersion device is started to assist dispersion; S4, keep the stirring speed 600r / min and the temperature 43-47℃, slowly add 1-3 parts by weight of modified polyacrylamide while stirring; after all the addition, continue stirring for 20 min; turn off the heating jacket, cool to room temperature naturally, keep the stirring speed 300r / min during the cooling; after the cooling, detect the viscosity, if the viscosity is too high, add a small amount of deionized water, stir for 5 min and then detect again until the viscosity is 500-800mPa•s; S5, filter the accelerator through a 100 mesh nylon filter to obtain the finished product.
8. The method for preparing a low-temperature adaptable early strength accelerator for sprayed concrete according to claim 7, characterized by, The stirring speed of the reactor in S1 is 500r / min; when adding aluminum sulfate, each interval is 5 min, and 1 / 3 of the total amount is added each time.
9. The method of claim 7, wherein the low temperature adaptable early strength accelerator for sprayed concrete is prepared by the steps of: In S2, the dropwise addition rate of triethanolamine is 1-2mL / s. 10. The application of the low-temperature adaptable early strength accelerator for shotcrete according to any one of claims 1-2 in the construction of shotcrete in a low-temperature environment of -5℃ to 5℃.
Citation Information
Patent Citations
Low-resilience high-performance sprayed concrete, spraying system and construction method
CN118757183A
Green low-carbon high-performance sprayed concrete using active regenerated micro-powder, and preparation method and construction process of green low-carbon high-performance sprayed concrete
CN119143440A